Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1152/jn.00287.2015
|View full text |Cite
|
Sign up to set email alerts
|

Differential encoding of spatial information among retinal on cone bipolar cells

Abstract: The retina is the first stage of visual processing. It encodes elemental features of visual scenes. Distinct cone bipolar cells provide the substrate for this to occur. They encode visual information, such as color and luminance, a principle known as parallel processing. Few studies have directly examined whether different forms of spatial information are processed in parallel among cone bipolar cells. To address this issue, we examined the spatial information encoded by mouse ON cone bipolar cells, the subpop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 109 publications
2
7
0
Order By: Relevance
“…The decorrelating surround effects are likely due to AC mediated inhibition in the inner retina, rather than horizontal cell (HC) mediated inhibition in the outer retina: First, mouse HCs (Peichl and González-Soriano, 1994) have little effect on BC (Purgert and Lukasiewicz, 2015) and RGC function (Cook and McReynolds, 1998;Taylor, 1999;Ichinose and Lukasiewicz, 2005). Second, we found that the GABAergic BC surround was gated by glycinergic signals (Fig.…”
Section: The Origin Of Bc Functional Diversitymentioning
confidence: 85%
“…The decorrelating surround effects are likely due to AC mediated inhibition in the inner retina, rather than horizontal cell (HC) mediated inhibition in the outer retina: First, mouse HCs (Peichl and González-Soriano, 1994) have little effect on BC (Purgert and Lukasiewicz, 2015) and RGC function (Cook and McReynolds, 1998;Taylor, 1999;Ichinose and Lukasiewicz, 2005). Second, we found that the GABAergic BC surround was gated by glycinergic signals (Fig.…”
Section: The Origin Of Bc Functional Diversitymentioning
confidence: 85%
“…It is proposed that all the retinal photoreceptors are merged via various retinal layers, i.e. the inner and outer plexiform layers, and other neural cells such as the amacrine cells [44][45][46][47][48]. We see the magnified representation of the initial image from close proximity, not unlike seeing images through a microscope or pair of binoculars.…”
Section: A Proposed Theory Of the Formation Of The 3d Default Spacementioning
confidence: 99%
“…Parallel processing of color and luminance make this possible. Furthermore, the spatial encoding properties of the ON-cone bipolar cells is determined by information received from amacrine cells [7]. AII amacrine cells are fundamental in the primary rod pathway because rod bipolar cells use AII amacrine cells to send information to ON-and OFF-cone bipolar cells [24,25].…”
Section: Due Tomentioning
confidence: 99%
“…The retina is the area in the back of the eye that contains light sensitive neurons, and is the first stage of processing visual information and sending it to the brain [5][6][7]. Within the retina are five types of neurons: photoreceptors, bipolar cells, ganglion cells, horizontal cells, and amacrine cells [5].…”
Section: Introduction To the Retinamentioning
confidence: 99%